"I Am Actually Sitting With Fear": Narratives of Fear of Crime and Actual Victimization in the Western Cape Province, South Africa. (March 2023) - Martin-Howard, Simone
In the Western Cape Province of South Africa, non-governmental organizations (NGOs) provide direct services for residents of underserved areas where gang violence is rampant. The purpose of this qualitative study is to create a context specific understanding of fear of crime, explore experiences of actual victimization, and identify the strategies participants use to adapt to community challenges at an NGO in the province through in-depth semi-structured interviews with Black and Colored women. Actual victimization was experienced by more than half of the sample, fear of crime was the main barrier for almost half of all participants to effectively use the NGOs services, and 40% of women adapt to community challenges by remaining resilient or coping with violence through avoidance.